Políticas de formação continuada e de avaliação para alfabetização: repercussões do PNAIC e da ANA no contexto da prática de escolas em Campina Grande/PB (2012-2018) - Mélo, Silmara Cássia Barbosa (2019)
This thesis analyzes the continuous training policies and literacy assessment, more specifically, the Pacto Nacional Pela Alfabetização na Idade Certa (PNAIC) and the Avaliação Nacional da Alfabetização (ANA) and the impact in schools from municipal teaching network of Campina Grande - PB, from 2012 to 2018. It is adopted as methodological and theoretical references, the Policy cycle approach of Stephen Ball and his collaborators, proposing an analysis of policy trajectory, by emphasizing the context of influence, text production context, and practice context. It is sought to solve the following issue: how do they articulate, in the context of neoliberal and managerial governmentality, the policies of continuous training and literacy assessment, established as of 2012, and which impacts in the context of practice in schools from municipal teaching network of Campina Grande, in Paraíba? This study comes from the assumption that continuous training policies and literacy assessment, inserted in the context of performativity and managerialism, are (re)contextualized and (re)organize pedagogical processes (training, planning, assessment, curriculum), enabling different ways of “practice” of policies in municipal teaching network of Campina Grande - PB. The main objective of this research is to analyze trajectory of PNAIC and ANA inserted in the context of neoliberal and managerial governmentality, as well as their connections and repercussions in the context of practice in schools from municipal teaching network of Campina Grande, Paraíba, from 2012 to 2018. To this end, the specific objectives are: analyze the assumptions and the policy networks that sustain the Brazilian educational policies for teacher training and education assessment; investigate which legal documents to mark the implementation of continuous training programs and the assessment policy for literacy nationally and in the municipal teaching network of Campina Grande - PB; examine the processes of (re)contextualization and (re)organization of practices (training, planning, assessment, curriculum) bearing in mind the guidelines of PNAIC and ANA in the municipal teaching network of Campina Grande; and to analyze the processes of “political acting” of PNAIC and ANA. It is determined that PNAIC and ANA são policies sustained by assumptions that aim to mobilize forces in the process of governance, seeing in education a propitious space for profit growth with a new market widespread by the neoliberal ideology.